The benefit of using plastic-covered mattresses and pillows on the frequency of asthma attacks in children with house dust mite allergy - Luh Putu Winansari Ratih; Hendra Santosa (Indonesian Pediatric Society, 2005)
Background House dust mite (HDM) is abundant in tropical ar-eas with an environmental temperature of 25-30 0 C and humidityof more than 50%. Minimizing exposure to HDM allergens will de-crease the frequency of asthma attacks in children with HDM hy-perreactivity.Objective To investigate the benefit of using plastic covered mat-tresses and pillows in decreasing the frequency of asthma attacksin children allergic to HDM.Methods This is a longitudinal analytical study on children aged3–12 years who showed positive HDM skin prick test (SPT). Thesubjects received communication, information, and education (CIE)for the first 3 months and CIE and plastic-covered mattresses andpillows for the second 3 months. The frequency of asthma attackswas observed for the two periods.Results Twenty-six children with asthma were included in this study,16 were boys and 10 were girls. SPT results were +2 in 17 chil-dren, +3 in 8 children, and +4 in 1 child, respectively. During theCIE as well as the CIE + plastic intervention periods, asthma at-tack frequency was decreased significantly in the 1 st , 2 nd , and 3 rdmonths. Among several variables (age, sex, SPT, atopic history infirst-degree relative, and other atopic history), age was the onlyone significantly related to asthma attack frequency.Conclusion Covering mattresses and pillows with plastic de-creased the frequency of asthma attacks in children with positiveSPT to HDM